ПЕРЕДОВИЙ ПЕДАГОГІЧНИЙ ДОСВІД ЯК ЕФЕКТИВНИЙ ЗАСІБ ФОРМУВАННЯ РЕФЛЕКСИВНИХ УМІНЬ СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2022)
The article is devoted to the problem of formation of students reflective skills in the process of gaining knowledge based on the advanced pedagogical experience.